Seismic multiple removal techniques : past, present and future - Verschuur, D. J. (Education tour series ;, 2013)
This book presents an overview of multiple removal methods that have been developed within the seismic exploration industry over the last five decades. It handles move-out based filtering, predictive deconvolution, wave equation-based prediction and subtraction and surface-related multiple removal, both for surface-related as well as internal multiples. The mathematical complexity is restricted to a minimum, while more emphasis is put at understanding the physical principles of these methods and their mutual relationships. The different multiple removal techniques are illustrated with a variety of synthetic and field data examples. For the surface-related multiple removal method, extra attenuation is paid to the practical aspects, extension to 3D data and land data applications. Finally, an outlook is given on how multiples can be turned from noise into usable data. --